The role of optical coherence tomography angiography biomarkers in assessing the outcome of long-term anti-VEGF therapy of diabetic macular edema - A. Zh. Fursova; A. S. Derbeneva; M. S. Tarasov; M. V. Vasil’eva; J. A. Gamza; N. V. Chubar (Российский офтальмологический журнал)
The purpose of the study was to assess the changes of biomarkers of diabetic macular edema activity by optical coherence tomography angiography (OCTA) data and the relationship of these biomarkers with the response to anti-VEGF therapy during a two-year follow-up. Material and methods. The study included 59 patients (101) eyes, averagely aged 60.27 ± 9.50 years. The average number of intravitreal injections of aflibercept over the treatment period was 12.87 ± 3.50. The initial size of the foveolar avascular zone (FAZ) area — 0.37 ± 0.22 mm2 , and the acircularity index — 0.56 ± 0.14 remained unchanged after 5 months: 0.36 ± 0.24 mm2  and 0.56 ± 0.12, respectively, and being practically in the same level in 12 and 24 months. The large FAZ area, noted in the group where disorganization of retinal inner layers (DRIL) was observed (0.39 ± 0.21 mm2 ), correlated with a lower visual acuity (r = 0.67, p = 0.003). The acircularity index remained unchanged; no significant differences were found in the DRIL patient groups. After 5 loading injections, the average initial density of vessels in the macular region increased from 12.33 ± 3.86 mm to 12.75 ± 1.14 mm, after 1 year it was 13.48 ± 1.15 mm, after 2 years — 13.25 ± 3.39 mm. The average density of retinal perfusion increased at the 5th month from 29.81 ± 10.85 % to 31.55 ± 2.34 %, after 12 months to 32.91 ± 3.45, and by the end of the observation period to 31.41 ± 9.79 %. In the DRIL group, the baseline vascular density and mean perfusion volume were significantly lower: 11.17 ± 2.09 mm vs. 13.49 ± 1.14 mm and 28.40 ± 4.53 % vs. 31.20 ± 2.44 %). Conclusion. DRIL, a biomarker reflecting impaired capillary blood flow in the superficial capillary plexus and correlating with functional results, can be used as a predictor of antiangiogenic therapy effectiveness. After antiangiogenic therapy with DMO, the microcirculation indices (FAZ and acircularity) remained stable, and the vascular density and perfusion volume tended to increase, which testifies to the absence of ischemic damage.